Performance evaluation of proactive, reactive, and hybrid routing protocols for small, medium, and large mobile ad hoc networks - Gatete, M.; Harubwira, F. (BOHR Journal of Computational Intelligence and Communication Network, 2024)
The popularity of wireless ad hoc networks is increasing daily. Examples of such networks are MANETs, VANETs, and Sensor networks. These types of wireless networks are dynamic and have different working features in common, and it is not always obvious to know which network type should be used given the needs of users. Determining the best protocols for a particular sort of wireless network’s problems is frequently another challenge. We evaluate the above-mentioned networks to fill this gap and ultimately demonstrate that MANET is the best option since it can be easily deployed anywhere, at any time, to meet the needs of the majority of users. For evaluation purposes, we used prominent network evaluation parameter metrics, i.e., End-to-end Delay, Network Throughput, and Packet delivery ratio. We compare three different MANET routing protocol types—PROACTIVE, REACTIVE, and HYBRID—one from each type; DSDV [Proactive], TORA [Hybrid], and AODV [Reactive]. The simulations and their results for both small and large systems were done on the OPNET simulator. According to MANET, DSDV outperforms other protocols in networks with high node densities in terms of the same metrics, while TORA performs better in networks with low node densities in terms of packet delivery ratio, end-to-end delay, and throughput.